A case of partial androgen insensitivity syndrome with undescended testis and clitoromegaly - Varma, Dixit; Mahela, Sangita; Ullah, Ibrahim Khalil; Mouli, Sharath C.; Sharma, Kritika; Singh, Gaurav; Baishya, Nirupam K.; Pathak, Jyotishmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Androgen insensitivity syndrome is a rare disorder of sex development that results from genetic mutations affecting the androgen receptor. Recently, we encountered a case of a 13-year-old individual who had been raised as female and sought medical attention for primary amenorrhea, which led to the discovery of partial androgen insensitivity syndrome. Early detection and gonad removal are necessary to mitigate the risk of cancer. Additional management steps such as corrective surgery and psychological support can also be valuable.